Depigmentasi Gingiva Menggunakan Teknik Bedah Scalpel pada Pasien dengan Hiperpigmentasi Gingiva : Sebuah Laporan Kasus - Negara, Mellani Cindera (Jurnal Kesehatan Gigi dan Mulut (JKGM), 2023)
Background: Gingival hyperpigmentation is a physiological pigmentation genetically, appearing with brown to black pigment on the gingiva and oral mucosa which is an aesthetic problem for patients. Purpose: This case report aims to discuss gingival depigmentation procedure using scalpel surgical techniques in patients with gingival hyperpigmentation. Case presentation: A 27-year-old female patient reported brown discoloration on the gums of her upper and lower front teeth which she had noticed ten years ago. Gingival depigmentation using scalpel surgical technique is performed to remove the pigment. Conclusion: Gingival hyperpigmentation is an aesthetic problem that is of concern to patients and requires surgical intervention to remove the pigment, one of them are gingival depigmentation with a scalpel surgery. Keywords: gingival depigmentation, gingival hyperpigmentation, scalpel surgery